Evaluation of the prevalence of opportunistic gram negative bacilli from the infections of oral cancer sites in comparison with non-cancer patients and assessment of the antibiotic resistance - Kibtia, Maria (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.